(untitled) (Journal of Applied Oral Science, 2024)
Oral soft tissue lesions require a precise diagnosis by oral biopsy with the ability to recognize these lesions within histopathological levels, so the instrument used for the incisions should be safe and cause little to no harm to the surrounding tissue. Objective: This study compared a dual-wavelength diode laser and an Er, Cr:YSGG laser in oral soft tissue incisions to determine the most effective and safest laser system at the histopathological level. Methodology: The (810 and 980 nm) dual-wavelength diode laser was used at 1.5 W and 2.5 W (CW) power settings, and the (2780 nm) Er, Cr:YSGG laser was used at 2.5 W and 3.5 W (PW) power settings. Both laser systems were used to incise the tissues of freshly dissected sheep tongue pieces to obtain the following histopathological criteria: epithelial tissue changes, connective tissue changes, and lateral thermal damage extent by optical microscopy. Results: The epithelial and connective tissue damage scores were significantly higher in the dual-wavelength diode laser groups than in the Er, Cr:YSGG laser groups (P<0.001), and there was a significant difference between some groups. The extent of lateral thermal damage was also significantly higher in the diode laser groups than in the Er, Cr: YSGG laser groups (P<0.001), and there was a significant difference between groups. Group 2 (2.5 W) of the diode laser was the highest for all three criteria, while group 3 (2.5 W) of the Er, Cr:YSGG laser was the lowest. Conclusion: The Er, Cr:YSGG laser with an output power of 2.5 W is, histologically, the most effective and safest laser for oral soft tissue incision. The dual-wavelength diode laser causes more damage than the Er, Cr:YSGG laser, but it can be used with a low output power and 1 mm safety distance in excisional biopsy.